Riding the wave of an expert: A successful talent development environment in kayaking - Henriksen, K.; Stambulova, N.; Roessler, K. K. (The Sport Psychologist, 2011)
The holistic ecological approach to talent development in sport highlights the central role of the overall environment as it affects a prospective elite athlete. This paper examines a flat-water kayak environment in Norway with a history of successfully producing top-level senior athletes from among its juniors. Principal methods of data collection include interviews, participant observations of daily life in the environment and analysis of documents. The environment was centered around the relationship between prospects and a community of elite athletes, officially organized as a school team but helping the athletes to focus on their sport goals, teaching the athletes to be autonomous and responsible for their own training, and perceived as very integrated due to a strong and cohesive organizational culture. We argue that the holistic ecological approach opens new venues in talent development research and holds the potential to change how sport psychology practitioners work with prospective elite athletes.